Macrophage migration inhibitory factor gene rs755622 G/C polymorphism and coronary artery disease: A meta-analysis of 8,488 participants - Li, Yan-yan; Wang, Hui; Zhang, Yang-yang (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims: Macrophage migration inhibitory factor (MIF) gene rs755622 G/C polymorphism was suggested to be associated with CAD risk. However, due to the different results among the individual studies, no agreement has been reached till now. Therefore, the meta-analysis on the association of MIF gene rs755622 G/C polymorphism with CAD was performed. Methods and Results: The association between them was evaluated by calculating the pooled odds ratios (ORs) and the corresponding 95% confidence intervals (CIs). The random effects models were used because of the significant heterogeneity among them. In this meta-analysis, 8,488 subjects from 9 studies were included. The MIF gene rs755622 G/C polymorphism was significantly associated with CAD under the allelic (OR: 1.213, 95% CI: 1.039-1.417, P=0.014), recessive (OR: 1.945, 95% CI: 1.214-3.115, P=0.006), dominant (OR: 0.781, 95% CI: 0.617-0.989, P=0.041), homozygous (OR:2.057, 95% CI: 1.289-3.284, P=0.003), and additive (OR: 1.327, 95% CI: 1.081-1.630, P=0.007) genetic models. Conclusions: MIF gene rs755622 G/C polymorphism was significantly related to CAD, especially in the Chinese population. The persons with the C allele of the MIF gene rs755622 G/C polymorphism might be susceptible to CAD.